2018
DOI: 10.20944/preprints201806.0112.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Water Extract of <em>Mytilus edulis</em> Suppresses Oxidative Stress and Improves Male Reproduction Dysfunction in High-Fat Diet-induced Obese Rats

Abstract: Obesity is a complex metabolic disease, which induces a variety of diseases, such as cardiovascular disease, type 2 diabetes, hypertension, and cancer. Various chemical agents can be used for treat obesity, but adverse some side effects, such cardiovascular disease and stroke. Natural products reported possessing anti-obesity activity. Mytilus edulis (ME) has been associated with some functional properties such as antioxidant and anti-inflammation. This study aims to determine the preventive effects of Mytilus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A high-fat diet (HFD) is a diet consisting of at least 35% of total calories consumed from fats, both unsaturated and saturated [1]. In addition to the popular processed foods, many other foods have a high fat content including but not limited to animal fat, chocolate, butter, and oily fish [2]. In a previous study, it was observed that High fat induces significant lobular inflammation, hepatocellular necrosis, hepatocellular ballooning, portal tract inflammation, pericellular and portal fibrosis as described.…”
Section: Introductionmentioning
confidence: 99%
“…A high-fat diet (HFD) is a diet consisting of at least 35% of total calories consumed from fats, both unsaturated and saturated [1]. In addition to the popular processed foods, many other foods have a high fat content including but not limited to animal fat, chocolate, butter, and oily fish [2]. In a previous study, it was observed that High fat induces significant lobular inflammation, hepatocellular necrosis, hepatocellular ballooning, portal tract inflammation, pericellular and portal fibrosis as described.…”
Section: Introductionmentioning
confidence: 99%